The Most Common Problems in Reading Components for Students with Learning Disabilities (The International Journal of Educational Sciences and Arts, 2024)
The current study aimed to identify the most common problems in the reading components among students with learning disabilities from the perspective of Arabic language course's teachers in government primary schools that contain learning disabilities programs in the education departments in Makkah Al-Mukarramah region, and to study the differences in knowledge levels according to the study variables. The final study sample consisted of (224) male and female teachers. To achieve the objectives of the current study, a descriptive survey approach was used, where a questionnaire was prepared as a tool for collecting data. The questionnaire consisted of (36) statements distributed over five dimensions. The results of the current study showed that the most common problems in the reading components among students with learning disabilities came at a level of (medium) agreement in general, with a general arithmetic mean of (3.155), while at the level of the sub-dimensions of the questionnaire, they all came at a level of (medium) agreement. The results also showed statistically significant differences in the total score averages of the questionnaire according to the gender variable in favor of male teachers, the number of years of experience variable in favor of male teachers who have experience from (1-5 years), and the workplace variable in favor of the education departments in the governorates of Makkah Al-Mukarramah and Taif, while the results showed no statistically significant differences in the total score averages of the scale according to the academic qualification variable. Based on the results reached, the researcher recommended several research recommendations and proposals, the most important of which is that the curriculum should include methods that motivate students to return to linguistic dictionaries and glossaries to search for the meanings of new vocabulary, and conduct additional studies aimed at discovering more scientific facts about the phenomenon of reading problems.
Keywords: Reading; Reading Components; Learning Disabilities; Students with Learning Disabilities